Hydrolysed poultry byproduct meal in extruded diets for cats - Bassi Scarpim, Lucas [UNESP]; de Ramos, Eloise Cristina [UNESP]; Graziele Pacheco, Leticia [UNESP]; Goloni, Camila [UNESP]; de Souza Theodoro, Stephanie [UNESP]; de Souza Ávida de Castro, Thaís [UNESP]; Carciofi, Aulus Cavalieri [UNESP] (Taylor & Francis, 2024)
Hydrolysed proteins have been shown to be potential ingredients in cat diets due to their high digestibility, presence of bioactive peptides, and relatively low antigenicity. The effects of the substitution of conventional low ash poultry byproduct meal (PBM) with hydrolysed poultry byproduct meal (HPM) as a protein source were evaluated in extruded cat diets. Five diets with similar nutrient contents were formulated: a control (CO) diet based on PBM and 4 diets with different inclusions of HPM (5%, 10%, 20%, and 30%, on an as-fed basis) replacing PBM as the protein source. The total tract apparent digestibility (CTTAD) of nutrients, faecal characteristics and microbial fermentation products, urine production and pH, nitrogen balance and urea renal excretion were evaluated using 30 healthy cats (15 males and 15 females; 4.18 ± 0.86 kg; 4.17 ± 1.38 years old), with 6 cats per diet in a complete randomised block design. When significant differences were found with the F test, the effects were evaluated by polynomial contrasts according to HPM inclusion (p < 0.05). The CTTADs of DM (89 ± 0.41%), CP (90 ± 0.36%), fat (93 ± 0.41%) and gross energy (90 ± 0.33%) were similar among treatments (p > 0.05). The faecal production, score, short-chain fatty acids and ammonia concentration were similar among treatments (p > 0.05). Isobutyric, isovaleric, valeric, and total branched-chain fatty acid contents increased quadratically (p < 0.05), with the highest level in the faeces of cats fed the diet with 20% HPM. Lactate concentration in faeces increased linearly with the inclusion of HPM (p < 0.05). Urine characteristics and urea renal excretion did not differ among treatments (p > 0.05). At 10% inclusion, HPM tended to increase the nitrogen retention of cats (p = 0.083), which may reflect the higher tryptophan, methionine, lysine, and available lysine contents of HPM in comparison to PBM. The inclusion of up to 30% HPM can be considered in cat formulations without affecting nutrient digestibility or faecal and urine characteristics. HPM tended to increase nitrogen retention and increased branched-chain fatty acids in faeces, aspects which deserves further studies.
Keywords: Branched-chain fatty acids; digestibility; felines; nitrogen balance